Airdrop sites location problem and resources distribution for emergency relief. (23rd December 2014) - Meng, Yan-ping; Huang, You-fang
In emergency relief, airdropping and distributing of emergency resources to disaster-affected areas can effectively alleviate the sufferings of disaster victims and prevent further loss of lives and properties. In this study, an airdrop sites location and distribution model is developed to consider the distribution gaps between airdrop sites and demands sites when the distribution related resources are scare. The total cost of emergency relief and distribution is optimised, including airdrop cost, distribution cost, and transferring cost of the distribution devices. A simulation consisting of 16 alternative airdrop sites was analysed. The results showed that the model and algorithm are effective tools for scheduling airdrop and distribution in disaster relief. The study contributes to emergency management and disaster relief by linking the selection of airdrop and distribution sites. The model can be extended to the situation of multi-type emergency resources, multi-stage rescue, etc., to enhance the adaptability to real emergency logistics system.